The Effectiveness of Online Advertising in Purchase Decision: Liking, Recall and Click - Lim, Y.; Yap; Lau, T. (INSInet Publications, 2011)
With the rapid advancement in the IT industry, many companies have made the Internet as part of their advertising media mix to take advantage of the online technologies. The Internet has become a popular advertising platform because marketers found that the Internet possess greater flexibility and control over the advertising materials. The aim of this research is to answer the question: “How significant are the measures of advertising effectiveness in terms of (1) attitude towards the ad, (2) ad recall, and (3) click-through rates in explaining online purchase decision.” All the three measures of advertising effectiveness were found to be significant predictors, with the ability to recall online ads being the most important predictor (Beta = 0.517), followed by the frequency of clicking online ads (Beta = 0.205) and attitudes toward online advertising (Beta = 0.163). The findings suggest that online advertising may be a powerful marketing tool in the context of online environment. The research findings also imply that marketers should include online advertising in their advertising media mix as online advertising promotes online buying or online shopping.